EFFECTIVENESS OF TELEMEDICINE HEALTHCARE SERVICES IN RURAL AREAS OF BANGLADESH: A STUDY ON SELECTED VILLAGES - Rahman, Md. Mafizur; Rahman, Md. Arifur (Universitas Airlangga, 2024)
Background: Bangladesh's healthcare system faces challenges in providing equitable access and quality healthcare to rural and remote communities compared to urban areas. To address these issues, the country has incorporated telemedicine into its healthcare system. Aims: This study aimed to assess the effectiveness of telemedicine services in rural Bangladesh. Methods: The study employed a mixed-method approach, including survey questionnaires and in-depth interviews. 100 participants were selected for the questionnaire survey for quantitative data, and 20 in-depth interviews were conducted to collect qualitative data. Results: The findings indicate that telemedicine has garnered a positive reception among rural residents. An overwhelming 86% regarded telemedicine as a cost-effective healthcare option. 44% reported accessing telemedicine services within 10 minutes, demonstrating their accessibility. Furthermore, a majority (54%) expressed satisfaction with telemedicine services. However, dissatisfaction was noted concerning the physical environment of the telemedicine centers. Conclusion: Overall, telemedicine in Bangladesh has proven effective in cost savings and time efficiency and has gained significant acceptance among rural residents. To further improve healthcare accessibility, expanding telemedicine centers to reach every remote union in Bangladesh is imperative. Additionally, raising awareness, providing ICT and telemedicine education, and ensuring affordable and reliable internet connectivity will maximize the potential of telemedicine services, ultimately benefiting underprivileged rural populations. Keywords: healthcare, rural Bangladesh, telehealth, telemedicine